Design of Corrugated Horn Antenna for LEO Satellite Feeding System: Efficient Hybrid Optimization Approach - Mahmoud Gadelrab; Shoukry I. Shams; Mahmoud Elsaadany; Ghyslain Gagnon (IEEE Access)
Low Earth Orbit (LEO) satellites are receiving fresh interest from the wireless communications society. The transceivers on these satellites require high-gain antennas with consistent performance over the operational spectrum. Corrugated horn antennas are the most typical feed used in such systems. Furthermore, several satellite systems use dual-polarized antennas to provide polarisation variety. However, simulating the full satellite feed transceiver is a time-consuming task. This paper presents a revolutionary hybrid technique that combines real-measured data with simulation tools to reduce the optimization time for the entire system while providing more accurate and robust results. This optimized design is fabricated using a CNC lathe machine with ±0.002 inches accuracy. The fabricated prototype is measured in an anechoic chamber, where the measured results are in good agreement with the simulated ones.